Profile of Guided Inquiry in Science Learning in Junior High Schools - Firdausy Rahma Agustiningrum Setiawan; Zainul Arifin Imam Supardi; Budi Jatmiko (IJORER : International Journal of Recent Educational Research, 2023)
Objective: This study aims to discover that guided inquiry is related to science learning at the high school and junior high school levels, which can increase students' knowledge in learning. The researchers also found that guided inquiry could only improve students' literacy skills to a moderate level, which indicated that guided inquiry was needed to improve these abilities. Method: The research method used is the literature review method by collecting sources that can be used as references or related references. Results: Based on the results of the literature review that has been carried out, it was found that the use of the guided inquiry learning model is proven to be an alternative to active science learning in terms of students' thinking and cognitive skills. Learning outcomes when applying the guided inquiry learning model follow the nature of science learning, including scientific attitudes, processes, products, and applications. Novelty: Research that previous researchers have carried out needs coordination with related parties, namely schools, which will also affect the research results. In addition, this research uses a lot of guided inquiry models rather than free inquiry models, which shows a less significant difference in the results to be achieved.